E-COMMERCE APPLICATIONS IN INCREASING CONSUMER ACCESS TO MUSLIM BOUTIQUE PRODUCTS USING THE WATERFALL METHOD - Moch Irwan Al Khafid; Nuril Lutvi Azizah; Yulian Findawati; Ade Eviyanti (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The research aims to develop an e-commerce application that enhances customer access to boutique fashion items through an efficient and user-friendly digital platform. Method: The system was designed using the Waterfall development model, supported by analytical tools such as flowcharts, entity relationship diagrams, and data flow diagrams, while MySQL was employed as the database structure. Results: The implementation of the web-based e-commerce application enabled customers to easily browse updated product information, select clothing models remotely, and complete transactions seamlessly. User feedback indicated high satisfaction, with 85% of respondents reporting that shopping became more convenient and enjoyable. Novelty: This study offers a focused digital solution tailored specifically for Muslim boutique SMEs, demonstrating how structured system design and web-based technologies can strengthen business competitiveness and expand market reach through accessible and culturally attuned e-commerce services.